2022
DOI: 10.1029/2022ja030586
|View full text |Cite
|
Sign up to set email alerts
|

Magnetosphere‐Ionosphere‐Thermosphere Coupling Study at Jupiter Based on Juno's First 30 Orbits and Modeling Tools

Abstract: We analyze the first 30 orbits of Juno to retrieve the properties of current systems and plasma flows associated with Jovian main auroras.• Southern hemisphere results are consistent with ionospheric plasma sub-corotation.• The two opposite patterns, sub-corotation and super-corotation, are observed in the northern hemisphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
28
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 91 publications
7
28
1
Order By: Relevance
“…They are strongly correlated with particle precipitations and are significantly enhanced within the main auroral regions, outside of which the conductances are expected to become smaller (e.g., Al Saati et al., 2022; Wang et al., 2021). Strobel and Atreya (1983) suggested that the Pedersen conductance ΣP ${{\Sigma }}_{P}$ is between 0.2 and 10 S , which is consistent with the values found with Juno data (Al Saati et al., 2022; Gerard et al., 2020; Wang et al., 2021). The Hall conductances ΣH ${{\Sigma }}_{H}$ are usually 2–3 times larger than the Pedersen conductances (Wang et al., 2021).…”
Section: Model Descriptionmentioning
confidence: 99%
“…They are strongly correlated with particle precipitations and are significantly enhanced within the main auroral regions, outside of which the conductances are expected to become smaller (e.g., Al Saati et al., 2022; Wang et al., 2021). Strobel and Atreya (1983) suggested that the Pedersen conductance ΣP ${{\Sigma }}_{P}$ is between 0.2 and 10 S , which is consistent with the values found with Juno data (Al Saati et al., 2022; Gerard et al., 2020; Wang et al., 2021). The Hall conductances ΣH ${{\Sigma }}_{H}$ are usually 2–3 times larger than the Pedersen conductances (Wang et al., 2021).…”
Section: Model Descriptionmentioning
confidence: 99%
“…However, two significant differences appear between our equatorial and these previous polar observations. First, the latter generally found a two-subregion structure with an upward FAC on the equatorward side and a downward FAC on the poleward side, except for a minor fraction of northern flybys for which Al Saati et al (2022) observed the opposite trend. In contrast, our study finds an additional downward FAC on the equatorward side of the upward FAC.…”
Section: Comparison With Juno Polar Observationsmentioning
confidence: 96%
“…By combining Juno multi-instrument data and modeling tools, Wang et al (2021) and Al Saati et al (2022) surveyed FACs and their other defined "MIT coupling Key Parameters" comprehensively during Juno magnetic footprint traversals of the main auroral emission. They found peak values of FACs (both upward and downward) in the northern and southern hemispheres of about 1 and 2 μA/m 2 , respectively.…”
Section: Comparison With Juno Polar Observationsmentioning
confidence: 99%
See 2 more Smart Citations